Grignard Reagent-Mediated Conversion of an Acyl Nitroso-Anthracene Cycloadduct to a Nitrone - Chen, Weibin (2006)
An intramolecular hetero-Diels-Alder cycloadduct of an acyl nitroso compound and a 9, 10-dimethyl anthracene derivative was prepared as a potential nitroxyl (HNO) donor. This compound did not release HNO under any of the conditions tested. Treatment of this cycloadduct with excess MeMgCl resulted in the formation of a nitrone, whose structure was confirmed by X-ray crystallography. A mechanism where MeMgCl acts as a nucleophile, strong base and Lewis acid possibly explains the formation of this product.